ChemInform Abstract: Visible‐Light‐Mediated Radical Aryldifluoroacetylation of Alkynes with Ethyl Bromodifluoroacetate for the Synthesis of 3‐Difluoroacetylated Coumarins. Issue 36 (September 2015) - Fu, Weijun; Zhu, Mei; Zou, Guanglong; Xu, Chen; Wang, Zhiqiang; Ji, Baoming
Abstract An ortho‐methyl‐substituted substrate does not react due to sterical hindrance.